1992
DOI: 10.1254/jjp.58.219
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Contractile Mechanisms by Carbachol and ATP in Detrusor Strips of Rabbit Urinary Bladder.

Abstract: Contractile mechanisms by carbachol and ATP were compared in the detrusor strips of rabbit bladder. To exclude modulation of the agonists-induced re sponses by intramurally synthesized prostaglandins, all the experiments were done in the presence of the potent cyclooxygenase inhibitor flurbiprofen (1 UM). The concentration-response curves for carbachol and ATP were shifted to the right by 6 10-fold by verapamil (10,uM), which abolished the K-induced contraction of the atropinized detrusor completely. A similar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
19
0

Year Published

1994
1994
2012
2012

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(20 citation statements)
references
References 30 publications
1
19
0
Order By: Relevance
“…Addition of a second or even a third different supramaximal stimulus further increased the isometric force. We proved that each of our stimuli are supramaximal by measuring the dose-response curves, which were comparable to other such curves in the literature -EFS [10,11], and CCh and K + [12,13]. It was shown earlier [14] that CCh, in doses which were too low to initiate a contraction, increased electrical field evoked submaximal contractions.…”
Section: Discussionsupporting
confidence: 82%
“…Addition of a second or even a third different supramaximal stimulus further increased the isometric force. We proved that each of our stimuli are supramaximal by measuring the dose-response curves, which were comparable to other such curves in the literature -EFS [10,11], and CCh and K + [12,13]. It was shown earlier [14] that CCh, in doses which were too low to initiate a contraction, increased electrical field evoked submaximal contractions.…”
Section: Discussionsupporting
confidence: 82%
“…22 Wu et al also reported that activation of muscarinic cholinergic receptors is not associated with membrane potential depolarization or the opening of L-type VGCCs but it can modulate L-type VGCCs via secondary voltage dependent membrane events, such as the suppression of K ϩ channel activity. 23 Therefore, these results suggest that the contribution of L-type VGCCs to CCh induced contraction is not as notable as that of KCl induced contraction.…”
Section: Discussionmentioning
confidence: 99%
“…Bladder smooth muscle contraction (neu ronal and muscarinic stimulation) depends upon a rise in intracellular free calcium, as a result of influx from extracellular spaces as well as release from intracellular stores (cal cium-induced calcium release) [6,7,[13][14][15][16][17][18]. Physiologically, thapsigargin exerts a marked effect on the response of isolated strips of bladder smooth muscle to neurogenic (field) stimulation and also direct receptor stimula tion (muscarinic cholinergic and alpha-adren ergic) [19,21,22], These effects are altered in response to partial outlet obstruction, indicat ing that contractile dysfunctions induced by partial outlet obstruction may be due in part to alterations in intracellular calcium uptake and storage into SR. Additional evidence for this comes from studies demonstrating a loss in calcium ATPase activity associated with contractile dysfunction secondary to partial outlet obstruction [26,27], Also a loss in SERCA protein is associated with partial out let obstruction [26,28].…”
Section: Discussionmentioning
confidence: 99%
“…On an intracellular basis, detrusor contraction, similar to that of all smooth muscles, depends upon the interaction of the contractile pro teins actin and myosin via phosphorylation of myosin light chains by myosin light chain kinase [4,5], In turn, phosphorylation of the myosin filaments depends upon a phasic in crease in intracellular free calcium concentra tion via calcium translocated from the extra cellular space and released intracellular bound calcium [6,7], Although there is an ini tial phasic response to stimulation, bladder emptying requires a sustained increase in in travesical pressure during urine expulsion [8][9][10]. Prior studies from our laboratory [ 10,11] and others demonstrated that the contractile response of the bladder to neuronal and mus carinic stimulation depends upon a rise in intracellular free calcium [12], resulting from both calcium influx from extracellular spaces and calcium release from intracellular stores (calcium-induced calcium release) [13][14][15][16][17][18], The participation of intracellular calcium in the response to stimulation involves thapsigargin-sensitivc calcium release from the sar coplasmic reticulum (SR) and calcium uptake into the SR by SR calcium activated ATPase (SERCA). Thapsigargin, a specific inhibitor of SERCA, has marked effects on the contrac tile response of the bladder to stimulation [19][20][21][22], Recently, thapsigargin-inhibitable enzymes have been located in cellular ele ments other than the SR; thapsigargin may not be as selective for SERCA as originally thought [23][24][25],…”
Section: Introductionmentioning
confidence: 99%